Early Life Intervention Using Probiotic Clostridium butyricum Improves Intestinal Development, Immune Response, and Gut Microbiota in Large Yellow Croaker (Larimichthys crocea) Larvae - Yin, Zhaoyang; Liu, Qiangde; Liu, Yongtao; Gao, Shengnan; He, Yuliang; Yao, Chuanwei; Huang, Wenxing; Gong, Ye; Mai, Kangsen; Ai, Qinghui (Frontiers in Immunology, 2021)
Marine fish larvae are vulnerable during the early life period. The early intervention using probiotics may be a promising method to improve growth of fish larvae. In this study, a 30-day feeding trial was conducted to evaluate the effects of early-life intervention using probiotic Clostridium butyricum (CB) on growth performance, intestinal development, immune response and gut microbiota of large yellow croaker (Larimichthys crocea) larvae. Four isonitrogenous and isolipidic diets were formulated with the supplementation of four different levels of CB (5×109 CFU g-1), 0.00% (Control), 0.10% (CB1), 0.20% (CB2) and 0.40% (CB3). Results showed that larvae fed diets with CB had significant higher final length than the control group. Meanwhile, larvae fed the diet with 0.10% CB had significant higher final weight and specific growth rate (SGR) than the control group. However, no significant difference in survival rate was observed among dietary treatments. CB supplementation significantly increased the height of intestinal villus and the length of intestinal enterocyte. Similarly, CB supplementation significantly increased the expression of tight zonula occludens-2 (zo-2) and ornithine decarboxylase (odc) than the control group. Larvae fed the diet with 0.20% CB had significant higher lipase and leucine-aminopeptidase (LAP) activity than the control group. Moreover, CB supplementation significantly improved immune enzyme activities than the control group. Sequencing of bacterial 16S rRNA V4-5 region indicated that dietary CB altered intestinal microbiota profile and decreased intestinal microbial diversities of larvae. CB supplementation could effectively increase the abundance of CB, and decrease the abundance of some potential pathogenic bacteria in larval gut. These results revealed that early-life intervention using 0.10%-0.20% CB could promote growth of large yellow croaker larvae probably through promoting intestinal development, improving immune enzyme activities and modulating gut microbiota.